Avaliação genética de clones de duas espécies de palma (Opuntia fícus-indica Mill e Nopalea cochenillifera Salm-Dyck) para fins forrageiros - Oliveira, Jacqueline de (2011)
The palm is well adapted to a forage arid and supports long periods of drought because of their morphological and physiological characteristics. This when provided as sole source of food for ruminants is no occurrence of diarrhea due to the low amount of protein. This study aimed to evaluate and select clones of cactus pear (Opuntia ficus-indica Mill and Nopalea cochenillifera Salm - Dyck) to increase the forage quality by increasing the amount of protein and decreasing the fiber content. The objective of this study was to evaluate and select clones of cactus pear (Opuntia ficus-indica Mill and Nopalea cochenillifera Salm - Dyck) to increase forage quality by increasing the amount of protein and decreasing the fiber content. The experiment was carried in the Experimental at the Horto Florestal an integrated unit of the Universidade Estadual de Feira de Santana-BAUEFS. We evaluated data from morphological and qualitative characteristics of the clones. For the morphological values for the height and width were increased, the overall average for the (giant) palm was 114.43 cm and 93.96 and 91.71 for the (miuda) and palm 108.98 cm. For chemical analysis the palm miuda held the highest average for the percentage of crude protein and lower crude fiber, 11.81 and 11.65% respectively. The clones behaved differently in each fertilization test, with differences between the clones, indicating genetic variability for selection. Fertilization that resulted in better performance of the clones was the organic fertilization. Based on the results obtained, we selected 20 superior clones, 15 giant and 5 miuda, to continue the program of cactus.